2010
DOI: 10.1007/978-94-007-0265-3_42
|View full text |Cite
|
Sign up to set email alerts
|

TRP Channels of Islets

Abstract: In the normal human body pancreatic β-cells spend most of the time in a READY mode rather than in an OFF mode. When in the READY mode, normal β-cells can be easily SWITCHED ON by a variety of apparently trivial stimuli. In the READY mode β-cells are highly excitable because of their high input resistance. A variety of small depolarizing currents mediated through a variety of cation channels triggered by a variety of chemical and physical stimuli can SWITCH ON the cells. Several polymodal ion channels belonging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 96 publications
1
47
0
Order By: Relevance
“…This effect was insensitive to thapsigargin (arguing against a storeoperated channel) and to Gd 3+ , a blocker of the Na + leak channel NALCN [38]. While the molecular identity of the P2Y 1 -activated leak channel remains unclear, candidates include members of the transient receptor potential channel family [39].…”
Section: +mentioning
confidence: 97%
“…This effect was insensitive to thapsigargin (arguing against a storeoperated channel) and to Gd 3+ , a blocker of the Na + leak channel NALCN [38]. While the molecular identity of the P2Y 1 -activated leak channel remains unclear, candidates include members of the transient receptor potential channel family [39].…”
Section: +mentioning
confidence: 97%
“…Several metabolites were described to function as activators of TRPM3 channels, including the steroid pregnenolone sulfate, lipid D-erythro-sphingosine, and L-type voltage-gated Ca 21 channel inhibitor nifedipine (Grimm et al, 2003;Wagner et al, 2008;Naylor et al, 2010;Islam, 2011). A comprehensive analysis of different compounds revealed that pregnenolone sulfate is currently the most powerful known activator of TRPM3 (Lesch et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Many biological functions have been connected with TRP channel activation, including regulation of Ca 2C homeostasis, tumorigenesis, sensory temperature, and pain sensation. In pancreatic b-cells, several members of the TRP family of cation channel proteins are expressed (Colsoul et al 2011, Islam 2011. The channels with the highest expression are TRPML1 and TRPP2.…”
Section: Introductionmentioning
confidence: 99%